SMART VILLAGE CONCEPT AND TOURISM DEVELOPMENT IN SUMBAWA REGENCY - Ivon Arisanti (Jurnal Riset Kajian Teknologi dan Lingkungan, 2019)
The complexity of the development problems faced by Sumbawa Regency nowadays require an acceleration to realize rural development-based development, especially the development of villages to become smart villages through: smart economy, smart mobility, smart environment, smart people, smart living, and smart government. These six elements are dimensions of Smart City that can be synergized with the development of Smart Village in advancing and developing the potential of Sumbawa Regency. The programs that can be carried out by the Sumbawa Regency Government in developing smart villages are based on the needs of each village such as the tepal village, one of the cultural villages, can attract tourists by making the bolic pan to strengthen cellular signals so that the internet is easier to accessed and tourism promotion can be intensified. For the village of Poto, the application of the command center in the village is expected to be able to easily access services and/or complaints. Services/complaints will be handled easily because they are connected to the application in the village office so that village officials can swiftly handle various complaints from the community. For this purpose, it is necessary to provide a Closed-Circuit Television (CCTV) display that can monitor the activities of the community in the village especially for the important access center such as village halls, schools and health centers. The CCTV can also display the SME products. Economic improvement through the empowerment of any potential in each village can be mastered by improving the functions and roles of MSMEs and cooperatives, providing facilities and infrastructure that support tourism development such as hotels, adequate road access, directions, flood-free roads, convenient parking, cooperation between stakeholders in increasing tourism, the availability of local products as souvenirs, a clean environment, and providing tourist information center in the strategic places making it easier for tourists when visiting.